Lidi Peeling Machine Technology in Pekan Sawah Village Kecamatan Sei Bingei Kabupaten Langkat - Utomo, Budi; Husni, Muhammad (Talenta Publisher, 2021)
Pekan Sawah Village is located in Sei Bingei District, Langkat Regency, North Sumatra Province. This village is 75 km from the city of Medan, which can be reached using a four-wheeled vehicle in 1.5 hours with the asphalt road conditions that are quite good. The residents of Pekan Sawah Village are generally the Karo tribe, which covers 80% of the total population. In general, the population is now doing business with oil palm, rubber, and only a small portion of them still maintains land farming businesses such as corn, long beans, etc. The high number of oil palm planters, which reaches 80% of the population, causes high unemployment in this village. This is because the work to carry out maintenance to harvest is very limited. But on the other hand there is oil palm leaf midrib waste which is a result of the castration process and or the oil palm fruit harvesting process itself. This waste is now made into sticks, which are then sold per kilo to the estimator, which is increasingly expensive and the available stock is very limited, while market demand is high. However, the residents experienced problems in trying to separate the sticks from the leaves. Work is done conventionally one by one so it takes a long time. This results in low productivity of sticks in this area. The entry of the USU Community Services Implementation Team raises new hopes for the community to be able to find solutions that are faced by this community. Complaints about the production of oil palm stick broomsticks were immediately raised by the traditional leaders in Pekan Sawah Village. The USU Community Services Implementation Team immediately formed a problem-solving team. Several lecturers were involved in this activity, including providing education on the correct disposal of palm oil waste for residents. This activity is also assisted by 5 students who have been trained to take action to solve this problem. Now the people of Pekan Sawah Village can increase their lid production using this stick machine.